Evaluation of research progress and trends on cement retarders application in oilwells: A bibliometric analysis of literature and stakeholders - Nwaichi, Peter Ikechukwu; Norida, Ridzuan; Nwaichi, Eucharia Oluchi; Gbonhinbor, Jeffrey Randy; Agi, Augustine Aja (Society of Petroleum Engineers, 2024)
Retarders are used to prevent hydration of oilwell cement by prolonging thickening time and setting time, giving enough time for cement slurry application under deep and high-temperature conditions. However, the history and potential research direction of oilwell cement retarder has not been fully investigated. Thus, this study aims to fill these gaps in knowledge by identifying the main themes, influential authors, reputable journals, countries, and emerging keywords in this research area. The VOSviewer software was used to analyze journal articles published between 2000 to 2022 from the Scopus database to achieve the history, emerging keywords and potential research direction of oilwell cement retarder. The results show that 1,217 research articles on oilwell cement retarders have been published. Additionally, emerging keywords such as alkaline-activated slags, inorganic polymers, geopolymers, curing, slag grouting, and magnesia have gained recent attention. Authors from China, the United Kingdom, the United States, Spain, and South Korea contributed over 50% of the cited publications within the selected years. The findings provide valuable insights into previous studies on cement retarder applications, allowing for a deeper understanding of the research area, identifying the research gaps, highlighting potential research directions and collaborators.